THE INFLUENCE OF INTERNET MEDIA ON THE LEARNING OF STUDENTS OF SMP NEGERI 1 PEUSANGAN BIREUEN DISTRICT - Faizin Faizin (Jurnal Scientia, 2023)
The concept of education today is more concerned with the activity and creativity of students (learners) than passively accepting knowledge from educators. For this reason, students are required to read more, one of the places to get reading material is internet media. The internet supports teaching and learning activity programs, especially improving teaching and learning achievement. The purpose of this study is that there is the influence of Internet Media one the Learning Students of SMP Negeri 1 Peusangan Bireuen Regency and can provide input for readers so that they can increase the use of internet media as a means of learning to improve learning outcomes. In this study, samples were determined randomly and data was collected by circulating questionnaires and documenting report card values. Next, the data were analyzed using t-test statistics. The results of this study showed t count < ttable (0.9940 < 1.66). This means that Internet Media Use does not influence The Learning of Students of SMP Negeri 1 Peusangan Bireuen Regency. Thus, it can be concluded that the internet is used by students more not for learning.